If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-5)-2(x+2)=-22
We simplify the equation to the form, which is simple to understand
4(x-5)-2(x+2)=-22
Reorder the terms in parentheses
+(+4x-20)-2*(x+2)=-22
Remove unnecessary parentheses
+4x-20-2+*(+x+2+)=-22
Reorder the terms in parentheses
+4x-20+(-2x-4)=-22
Remove unnecessary parentheses
+4x-20-2x-4=-22
We move all terms containing x to the left and all other terms to the right.
+4x-2x=-22+20+4
We simplify left and right side of the equation.
+2x=+2
We divide both sides of the equation by 2 to get x.
x=1
| 3e-4=-2 | | 2+14a=-8+9a | | 7y+18=180 | | 60x^2-20xy+12x=0 | | -7(a-6)=2-2a | | 4(x-3)=2x+2(x-6) | | 2x^6-17x^4+17x^3= | | 15x+45=180 | | ba-4b=c | | .5x+3=2 | | 6x^3-9x^2-216x+9=0 | | 25=-8+2(s-4) | | 3(a+b)=f | | 35x^2-9x-2=0 | | (-6x+7)=(19x-1) | | 9y+4-7y=124 | | -10(x-1)=-10x | | 0=4x^2+39x-10 | | -5b+6(1-b)=83 | | 2x^4-x^3-9x^2+13x-4=0 | | y-5=7(x-6) | | 2x^4-x^3-9x^2+13-4=0 | | b-a=d | | p^3-3p+2=0 | | 18y+3y=6 | | s(4+p)=m | | X+3.2=7.5 | | 5(+4)=18-9 | | 3(4-6k)+1=-131 | | 3y+18y=6 | | 36x^2-48x+16=1 | | -5q-2(1-q)=-6q |